THE USAGE OF BAGASSE PULP FOR WOOD FIBER SUBSTITUTION IN PAPERMAKING - Darono Wikanaji; Trismawati ,; Pepi Kartiko (Center for Pulp and Paper, 2012)
Research of virgin bagasse pulp and market bagasse pulp as the furnish for MG tissue 17 gsm, HVS paper 56 gsm, and BC paper 210 gsm has been done for NBKP and LBKP substitution. MG tissue was produced on PM 4th at 3,2% lower speed and 6,7% lower throughput is able to replace the whole LBKP portion (± 60%) with no negative effect on physical properties at all. The use of bagasse pulp up to 15% to substitute LBKP in the furnish of HVS produced on PM 5th. at 4,3% lower speed and 1% higher throughput is able to improve strength index, tensile index, and tear index, and reduces the porosity up to 800 ml/minute. Bagasse pulp for BC paper was produced on PM 2nd. at the same speed and throughput is able to replace some portion of LBKP (40 – 80%) and NBKP (10 - 20%) with apparently no negative effect on physical properties. But, properties of BC still on between the high and low level properties of BC available on the market, even though a sharp decrease of strength index, tear index and double fold has been found when compared to BC 210 gsm using 20 - 30% NBKP.Keywords: bagasse pulp, tensile index, strength index, tear index, porosity ABSTRAK Penelitian pulp bagas virgin dan bagas pasaran sebagai bahan baku pembuatan kertas tisu gramatur 17 g/m2, kertas HVS 56 g/m2, dan karton BC 210 g/m2 dalam rangka substitusi serat LBKP dan NBKP telah dilakukan. Kertas tisu MG yang dibuat di PM4 pada kecepatan 3,2 % lebih rendah dan 6,7 % kapasitas lebih rendah ternyata mampu mensubstitusi seluruh porsi LBKP (60%) tanpa efek negatif pada sifat fisik kertas. Kertas HVS dibuat di PM5 pada kecepatan 4,3 % lebih rendah dan kapasitas 1 % lebih rendah ternyata mampu meningkatkan indeks kekuatan, indeks tarik, dan indeks sobek, serta mengurangi porositas hingga 800 ml/mnt. Karton BC dibuat di PM2 pada kecepatan dan kapasitas yang sama ternyata mampu mensubstitusi porsi LBKP (40 – 80 %) dan NBKP (10 – 20 %) tanpa pengaruh negatif pada sifat fisik. Tetapi sifat BC masih berada diantara batas bawah dan batas atas BC komersial, meskipun ada penurunan tajam pada indeks kekuatan dan ketahanan lipat dibandingkan dengan BC yang menggunakan 20 – 30 % NBKP.Kata kunci : pulp bagas, indeks tarik, indeks kekuatan, indeks sobek, porositas